The Effect of Project-Based Learning (PjBL) Assisted by Miniature Media on Students' Learning Outcomes and Creative Thinking Skills in Solar System Material - Simanjorang, Duma Sari; Silaban , Ramlan (ISER (Indonesian Science Education Research), 2025)
Science learning media play an important role in the learning process because science is closely related to everyday life and helps students understand themselves and their environment. This study aims to examine the effect of the Project-Based Learning (PjBL) model assisted by miniature media on students’ learning outcomes and creative thinking skills in the solar system topic at SMP Negeri 17 Medan. This research used a quasi-experimental method with a pretest-posttest control group design for learning outcomes and a one-posttest control group design for creative thinking. The sampling technique applied was cluster random sampling, where each class was treated as a cluster. Two classes were randomly selected as samples: class VII-2 as the control group receiving conventional instruction, and class VII-3 as the experimental group taught using the PjBL model assisted by miniature media. The research instruments consisted of a multiple-choice learning achievement test and a creative thinking observation sheet based on Torrance’s indicators of fluency, flexibility, originality, and elaboration. The instruments were validated by experts and pilot-tested to ensure validity and reliability. Data were analyzed using a one-tailed t-test with SPSS version 30. The results indicated that students taught using the PjBL model with miniature media achieved higher learning outcomes and creative thinking skills than those taught conventionally. The t-test results showed significance values of 0.001 < 0.05 for both learning outcomes and creative thinking. Therefore, the PjBL model, assisted by miniature media, positively and significantly influences students’ learning outcomes and creative thinking skills on the solar system topic at SMP Negeri 17 Medan.